The Influence of Mobile Legends Online Games on The Aggressive Behavior of Undergraduate Social Science Education Students - Bilgis Ruman Azzahra; Musyafah Mia Kurniati; Armawati Hidayati (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
The online game Mobile Legends is an online game with a war theme, so it is often the cause of momentary emotions in players (aggressive behavior). Mobile Legends is a team-based game that works together to achieve certain goals in the game. Basically, this game will have both negative and positive impacts on the players. So this research will provide readers with insight into improving their experience of playing online games without behaving aggressively. Apart from that, this research also aims to determine the influence of the online game Mobile Legends on the aggressive behavior of students of the 2022 Social Sciences Education Undergraduate Study Program, Surabaya State University. This research used a qualitative descriptive research method, namely the data needed for this research was collected using data collection techniques through online observations distributed using Google from and focus group discussions (FGD). According to the results of the FGD that we conducted together, it was stated that the online game Mobile Legends was an escape for the 2022 class of Social Sciences education undergraduate students at Surabaya State University when they were experiencing stress due to the many problems they were experiencing. So this will have a negative influence and cause aggressive behavior in the players.